Lewis Nathaniel Chase papers - Chase, Lewis Nathaniel, 1873-1937.; Chase, Emma Lester, 1885-; Chase, Pearl-Adell, 1872-1955.
Correspondence, diaries, writings, lecture notes, student papers, family papers, biographical matter, scrapbooks, printed matter, and other papers relating to Chase's career as an author, editor, and professor of English literature in various universities in the United States and abroad, including India and China. Includes editorial correspondence with American and English authors including Conrad Aiken, Walter De la Mare, Robert Frost, Thomas Hardy, A.E. Housman, Edgar Lee Masters, Edna St. Vincent Millay, and Edward Arlington Robinson; and correspondence with actors, artists, and musicians. Also includes correspondence, diaries, writings, poetry, notes, and other papers of Chase's first wife, Pearl-Adell Chase; his second wife, Emma Lester Chase; and other family members.
Editor, author, and educator.
Collection material in English, with French.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Aiken, Conrad, -- 1889-1973 -- Correspondence; De la Mare, Walter, -- 1873-1956 -- Correspondence; Frost, Robert, -- 1874-1963 -- Correspondence; Hardy, Thomas, -- 1840-1928 -- Correspondence; Housman, A. E. -- 1859-1936 -- Correspondence; Masters, Edgar Lee, -- 1868-1950 -- Correspondence; Millay, Edna St. Vincent, -- 1892-1950 -- Correspondence; Robinson, Edwin Arlington, -- 1869-1935 -- Correspondence; Chase family; Actors -- Correspondence; American literature; Americans -- China; Americans -- India; Artists -- Correspondence; Authors, American -- Correspondence; Authors, English -- Correspondence; English literature; Literature; Literature -- Study and teaching -- China; Literature -- Study and teaching -- India; Literature -- Study and teaching -- United States; Musicians -- Correspondence; Poetry; Authors; Editors; Educators